2, 3-di(2-furyl) quinoxaline bearing 3 -ethyl rhodanine and 1, 3 indandione based heteroaromatic conjugated T-shaped push -pull chromophores: Design, synthesis, photophysical and non-linear optical investigations. (February 2020) - Gopi, Vidya; Subbiahraj, Saravanan; Chemmanghattu, Karthika; Ramamurthy, Praveen C.
Abstract: The design, synthesis, computational, spectroscopic, and, the second and third order non-linear optical studies of a two new π-deficient cross-conjugated T-shaped push-pull molecules (QFR and QFI ) consisting of 3-ethyl rhodanine and 1, 3 indandione substituted with heterocyclic quinoxaline ring were synthesized by Knoevenagel condensation reaction of the precursor dialdehydes with active dye molecules were described in detail. In the as synthesized molecule, the electron donating thiophene moiety acts as an efficient π-bridge on either side to the quinoxaline core that permits good viability in fine-tuning the optical absorption spectrum with good solubility. The computational studies of these molecules show efficient intra molecular charge transfer (ICT) processes analyzed through their molecular orbital characteristics, excitation energy, absorption maxima, oscillator strength and Mulliken population analysis. The comparison study between the structures of these push-pull molecules were done by their photophysical characteristics including CIE coordinates; thermal characteristics, XRD studies and electrochemical analysis. The time-resolved fluorescence spectra with nanosecond time profile were measured to detect the delayed fluorescent performance of the push-pull molecules QFR and QFI . Hyper-Rayleigh scattering (HRS) in chloroform solution of varying concentrations, using a standard wavelength at 1064 nm was used to assess their first order hyperpolarizability. Optical non-linear property was again proved by open-aperture Z-scan technique investigated at 532 nm and the observed optical limiting behavior was originated from the reverse saturable absorption (RSA) process. The second and third order NLO studies reveals that 3-ethyl rhodanine substituted QFR molecule ( β value from HRS, 84.64 × 10 −30  esu and β e f f from Z scan, 10 × 10 −10  m/W) shows high non-linear optical properties and thermal stability compared with 1, 3 indandione substituted QFI ( β value from HRS, 48.00 × 10 −30  esu and β e f f value from Z scan, 2 × 10 −10 m/W). Highlights: Two new push-pull Quinoxaline based T-shaped molecules containing strong terminal acceptor units were synthesized. Computational and optical studies confirm the ICT characteristics of the molecules. Second order and third order NLO characteristics confirmed from HRS and Z scan.